A hydrophobic coating on cellulose nanocrystals improves the mechanical properties of polyamide-6 nanocomposites. (May 2022) - Benkaddour, Abdelhaq; Demir, Eyup Can; Jankovic, Nicole C; Kim, Chun Il; McDermott, Mark T; Ayranci, Cagri
Recent demands for high-performance lightweight materials have brought researchers' attention to various nanoparticles to reinforce polymeric materials. As such, sustainable and stiff cellulose nanocrystals (CNC) have become a popular candidate as nano-reinforcements. While CNC can offer great advantages, such as high mechanical properties and low density, it might agglomerate even in hydrophilic polymers because of its strong affinity to itself (intra and intermolecular hydrogen bonds) which prevents its broader use in industrial applications. This study aims to improve the compatibility between CNC and polyamide 6 (PA6) by a chemical modification that produces a surface polarity drastically different from non-modified CNC. The surface of CNC was rendered by the covalent coupling of stearic acid (SA) to the surface hydroxyl groups to produce stearate modified CNC (CNC SA). The effect of the modification was analyzed for CNC SA reinforced PA6 nanocomposites, and the results are compared to that of non-modified CNC reinforced PA6 samples. The addition of unmodified CNC to PA6 provided a modest improvement while the addition of CNC-SA provided substantial improvement on the modulus and tensile strength of the nanocomposite films.